Konstruksi Hukum Pengawasan Internal terhadap Tindakan Koruptif Aparatur Sipil Negara (APIP): Studi Kasus Fee Proyek di Kementerian Pertanian - Wati, Linda Rahma; Adzkia, Nurul; Vianka, Tania Putri; Barus, Sonia Ivana; Iskandar, Iskandar (Journal of Contemporary Law Studies, 2025)
This research examines the legal construction of internal supervision by the Government Internal Supervisory Apparatus (APIP) in tackling corrupt acts committed by the State Civil Apparatus (ASN), with a case study of project fees at the Ministry of Agriculture. Corruption in the bureaucracy, especially through the practice of project fees, shows the weakness of the internal control system, even though it has been regulated in regulations such as Government Regulation Number 60 of 2008 concerning the Government Internal Control System (SPIP) and Government Regulation Number 94 of 2021 concerning Civil Servant Discipline. Through a normative juridical approach and case studies, this research found a gap between legal norms and their implementation. APIP, as the main instrument of supervision, still faces challenges in terms of independence, competence, and adequate structural support. Cases in the Ministry of Agriculture show that supervisory actions are often reactive, not preventive. Therefore, it is necessary to strengthen the role of APIP through the adoption of integrity audit methodology (probity audit), human resource capacity building, and institutional reform in order to realize effective, independent, and accountable supervision. This research offers legal and institutional recommendations to strengthen clean and integrity governance.